The secret of Wildcat Swamp - Dixon, Franklin W. (New York : Grosset & Dunlap, 1969)
An archaeological expedition in the West turns into a desperate attempt to capture robbers and an escaped convict
Keywords: Detective and mystery stories; English fiction